Effect of adenine on the synthesis of purine derivatives in wheat seedlings - Hanna Rybacka (Acta Societatis Botanicorum Poloniae, 2015)
The effect of adenine and other purine derivatives on the "de novo" purine synthesis was investigated in young wheat schoots. Adenine, adenosine and AMP inhibited strongly this biosynthesis, whereas hypoxanthine had no effect. The incorporation of each of the used precursors; [l-14C] glycine, [14C] formate and [14C] carbonate was inhibited by adenine in the same extent.